Alternative Splicing and DNA Damage Response in Plants - Nimeth, Barbara Anna; Riegler, Stefan; Kalyna, Maria (Frontiers in Plant Science, 2020)
Plants are exposed to a variety of abiotic and biotic stresses that may result in DNA damage. Endogenous processes, such as DNA replication, DNA recombination, respiration or photosynthesis, are also a threat to DNA integrity. It is therefore essential to understand the strategies plants have developed for DNA damage detection, signaling, and repair. Alternative splicing (AS) is a key post-transcriptional process with a role in regulation of gene expression. Recent studies demonstrate that the majority of intron-containing genes in plants are alternatively spliced, highlighting the importance of AS in plant development and stress response. Not only does AS ensure a versatile proteome and influence the abundance and availability of proteins greatly, it has also emerged as an important player in the DNA damage response (DDR) in animals. Despite extensive studies of DDR carried out in plants, its regulation at the level of AS has not been comprehensively addressed. Here, we provide some insights into the interplay between AS and DDR in plants.